Re-considering language within a cosmopolitan understanding: Toward a multilingual franca approach in international business studies - Janssens, Maddy; Steyaert, Chris (Journal of International Business Studies, 2014)
This paper aims to uncover the normative assumptions that guide language studies in international business. Relying on sociolinguistics and cosmopolitan theory, we point to the possibility of conceiving language as a social practice rather than a discrete entity, and understanding globalization as the entanglement between universality and particularity rather than treating these two notions separately. Combining these linguistic and global assumptions, we arrive at three different research approaches to study linguistic performances in global work settings: monological lingua franca, monological multilingualism and multilingual franca. As the latter approach is unexplored, we develop the third option which underlines a human-centered multilingualism that conceives language as a social activity in which speakers mobilize multiple linguistic resources to express voice. The advantages of such an approach are its ability to capture the complexities of contemporary global life and its emphasis on a new understanding of multilingualism and diversity that truly goes beyond any kind of monolingualism. In terms of practice implications, a multilingual franca approach provides space for emancipatory politics through allowing mixed language use.